Certain Aspects of "Labour Discipline" Term Interpretation - Andrey Valerievich Dvoretsky; Angelika Olegovna Gavrilova (Сибирское юридическое обозрение, 2012)
The special place during the Soviet and post-Soviet periods was taken by the main researches of the labour discipline. In the science there were attempts of defining the concept "the labour discipline", which included economical, legal, organizational, psychological and other factors. The article is devoted to the development of understanding the term "the labour discipline", methods of its study and the components of its concept.